Implementasi Kebijakan Penatausahaan Aset Tetap Barang Milik Negara Pada Kepolisian Daerah Kalimantan Tengah: Implementation Of State Assets Of State-Owned Goods Policy On The Policy Of The Central Kalimantan - Hidayat, Noor; Sitepu, Deni Patri Nasrani (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2015)
This study aims to find out, explain, and describe the Implementation of State-Owned Property Assets Administration Policy in the Central Kalimantan Regional Police. The type of research used in this study is descriptive with a qualitative approach using data based on facts obtained in the field. The primary data type is the Central Kalimantan Regional Police chief and staff, Operator SIMAK BMN, Head of the Ministry of Finance Palangka Raya's Wealth Services Section. While secondary data comes from the results of documentation in library sources. The technique of collecting data uses observation, interviews, and documentation. Based on the results of the analysis of the data obtained, it is known that the implementation of the Administration of Fixed Assets of State Property in the Central Kalimantan Regional Police has not been carried out optimally because of communication, disposition, resources and bureaucratic structures that have not been maximized